Comparative Study Of Iterative Search Method For Adaptive Filtering Problems. - Ahmad, N.A (2005)
Adaptive filtering problem refers to a class of application in signal processing that deals with adaptation of a system so as to adjust itself with the phenomenon that is taking place in its surrounding. Examples of such problem include adaptive system modeling, noise cancellation, equalization and prediction.